Identifying key m6A-methylated lncRNAs and genes associated with neural tube defects via integrative MeRIP and RNA sequencing analyses - Yang, Jing; Xu, Jing; Zhang, Luting; Li, Yingting; Chen, Min (Frontiers in Genetics, 2022)
Objective: N6-methyladenosine (m6A) is a common post-transcriptional modification of messenger RNAs (mRNAs) and long non-coding RNAs (lncRNAs). However, m6A-modified lncRNAs are still largely unexplored. This study aimed to investigate differentially m6A-modified lncRNAs and genes involved in neural tube defect (NTD) development. Methods: Pregnant Kunming mice (9–10 weeks of age) were treated with retinoic acid to construct NTD models. m6A levels and methyltransferase-like 3 (METTL3) expression were evaluated in brain tissues of the NTD models. Methylated RNA immunoprecipitation sequencing (MeRIP-seq) and RNA sequencing (RNA-seq) were performed on the NovaSeq platform and Illumina HiSeq 2500 platform, respectively. Differentially m6A-methylated differentially expressed lncRNAs (DElncRNAs) and differentially expressed genes (DEGs) were identified, followed by GO biological process and KEGG pathway functional enrichment analyses. Expression levels of several DElncRNAs and DEGs were evaluated by quantitative reverse transcription-polymerase chain reaction (qRT-PCR) for validation. Results: m6A levels and METTL3 expression levels were significantly lower in the brain tissues of the NTD mouse model than in controls. By integrating MeRIP-seq and RNA-seq data, 13 differentially m6A-methylated DElncRNAs and 170 differentially m6A-methylated DEGs were identified. They were significantly enriched in the Hippo signaling pathway and mannose-type O-glycan biosynthesis. The qRT-PCR results confirmed the decreased expression levels of lncRNAs, such as Mir100hg, Gm19265, Gm10544, and Malat1, and genes, such as Zfp236, Erc2, and Hmg20a, in the NTD group. Conclusion: METTL3-mediated m6A modifications may be involved in NTD development. In particular, decreased expression levels of Mir100hg, Gm19265, Gm10544, Malat1, Zfp236, Erc2, and Hmg20a may contribute to the development of NTD.